Strategi Pemasaran Dan Harga Pada Produk Somethinc - Novi Pujiastuti Ramadhani; Desy Fitriyani; Mohamad Zein Saleh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study uses qualitative methodology to analyze how marketing strategies and prices exist on Somethinc products. Literature review is also obtained to be able to process data. The results of this study show that Somethinc products are very racing on social media for how they promote the product and pricing strategies that are carried out in various ways to achieve the desired target. The objectives in this study are: 1) To be able to find out the marketing strategy carried out by Somethinc products. 2) To be able to know how the pricing strategy set by Somethinc product.